DETECTION OF CRYPTOSPORIDIUM SPECIES IN CATTLE AND HANDLERS BY MOLECULAR TECHNIQUE IN WASIT PROVINCE - Hasan, Murtadha Kadhim; Mohan, Zahraa Hamid; Saeed, Farah Mohammed; Mahdi, Oras Abdulsayed; Abdulhussein, Rasha Hamzah; hamzah, Sarah Hussein; Kareem, Mustafa basim (Journal of Medical Genetics and Clinical Biology, 2024)
I collected 300 cow feces samples (130 males - 170 females) and used molecular analysis to detect the parasite. The results showed significant differences (p ≤ 0.05) between the infection rate using particle technology of 38% (38/100) and 41% (41/100) in cows and breeders, respectively, while traditional microscopic methods showed 21% (21/100) and 17% (17/100) in cows and breeders, respectively. DNA sequence analyzes of 10 isolates from infected cows identified four species of the Cryptosporidium parasite genus which included: C. parvum (6/10), C. andersoni (2/10), C. bovis (1/10) and C. ryanae (1/10. The species C. andersoni, C. parvum, C. bovis and C. ryanae have been genetically confirmed through DNA sequence analysis, and it is considered the first recording of these species in local cattle in Iraq. In breeders, three types of the Cryptosporidium parasite were recorded through DNA sequence analysis in 10 isolates from infected individuals, which included: C. parvum (2/10), C. andersoni (5/10) and C. hominis (3/10). It is considered the first recording of this species among breeders in Iraq.